Development of encapsulated Trichoderma harzianum UPM40 against Sclerotium rolfsii on chili plant - Adzmi, Fariz (2018)
Trichoderma as a biological control agent is widely used in sustainable agriculture. Commercialisation of this product in large scale with suitable formulation is still remains a problem especially to ensure the viability and efficiency of the formulation upon application in the field. Encapsulation method has emerged as sophisticated technique to develop the formulation of biological control agents. Encapsulation is the process of entrapping an active ingredient to shield it from adverse environmental conditions. Encapsulation of biological control agents (BCA) enables the creation of a microenvironment wherein the viability of the cells is maintained for storage, controlled release, and easy delivery. Encapsulation technique using extrusion method was used to prepare Trichoderma harzianum UPM40 beads. Based on the physical characterisation, a formulation with 2% (w/v) alginate, 1% (w/v) montmorillonite clay (MMT), and 5% (w/v) starch was able to produce T. harzianum UPM40 beads. This formulation produced almost perfectly shaped beads with SF 0.041 ± 0.006. It also offered a good swelling ability (62.11%) and less shrinkage (48.48%) during the drying process. Chemical characterization using the Fourier Transform Infrared Spectroscopy (FTIR) showed the interaction between the functional groups of alginate, MMT, and starch in the alginate- MMT-starch beads. It was shown by the shifting characteristic peaks of COO⁻ from starch at 1602 to 1610 cm⁻¹. Next C-O-C of alginate shifted from 1024 to 1002 cm⁻¹. Lastly, Si-O bending of MMT shifted from 405 to 453 cm⁻¹. Thermogravimetric analysis (TGA) showed an improvement in the thermal stability of the alginate-MMT-starch compared to alginate-MMT beads. X-ray Diffraction Analysis (XRD) shows the intercalation and exfoliation between starch and MMT. Peak for starch at 2θ° (15.06°) was shifting to 2θ° (16.64°) while peak at 2θ° (8.8°) for MMT was disappear in alginate-MMT-starch. Scanning electron microscopy (SEM) revealed a homogeneous distribution of MMT and starch particles throughout the alginate linkage. The surface area and pore diameter were 4.46 m²/g and 38.2 Å, respectively. Thus, T. harzianum UPM40 was successfully encapsulated in the alginate–MMT–starch beads. Storage analysis of the encapsulated T. harzianum UPM40 showed that low storage temperature (5 °C) was significantly better (p < 0.05) compared to at room temperature (30 °C). At low temperature, T. harzianum UPM40 beads maintained its viability of 6.59 log cfu/g up to seven months. The T. harzianum UPM40 beads were tested as a biological control agent against a soil-borne pathogen, S. rolfsii. In a dual culture, T. harzianum UPM40 displayed strong antagonistic activity against S. rolfsii. The percentage of inhibition of radial growth (PIRG) was 58.12%. Efficacy test of T. harzianum UPM40 for suppressing soil-borne diseases caused by S. rolfsii was conducted on chilli plants. Disease assessment results showed significant differences in disease incidence and disease severity index. T. harzianum UPM40 beads suppressed S. rolfsii with disease reduction of DI at 88.46% and DSI at 72.80%.